Pyoderma gangrenosum with renal and splenic impairment - case report - Luciana Rabelo de Carvalho; Virgínia Vinha Zanuncio; Bernardo Gontijo (Sociedade Brasileira de Dermatologia, 2013)
Pyoderma gangrenosum is an uncommon and recurrent neutrophilic dermatosis of unknown cause. The lesions usually start as tender sterile papulopustules or erythematous nodules that undergo necrosis followed by ulceration. The lower limbs are most commonly affected and around half of the cases are associated with systemic disorders. Although rare, cases of pyoderma gangrenosum with extramucocutaneous sterile neutrophilic infiltrate have been reported, with the lungs being the most commonly affected organ. We report a case of pyoderma gangrenosum with splenic and renal impairment. Pyoderma gangrenosum should be considered a multisystemic disease with classic cutaneous manifestations and potential involvement of internal organs.